Sleep in the Acute Phase of Severe Traumatic Brain Injury: A Snapshot of Polysomnography. (September 2016) - Wiseman-Hakes, Catherine; Duclos, Catherine; Blais, Hélène; Dumont, Marie; Bernard, Francis; Desautels, Alex; Menon, David K.; Gilbert, Danielle; Carrier, Julie; Gosselin, Nadia
Background and Objectives . The onset of pervasive sleep-wake disturbances associated with traumatic brain injury (TBI) is poorly understood. This study aimed to ( a ) determine the feasibility of using polysomnography in patients in the acute, hospitalized stage of severe TBI and ( b ) explore sleep quality and sleep architecture during this stage of recovery, compared to patients with other traumatic injuries. Methods . A cross-sectional case-control design was used. We examined the sleep of 7 patients with severe TBI (17-47 years; 20.3 ± 15.0 days postinjury) and 6 patients with orthopedic and/or spinal cord injuries (OSCI; 19-58 years; 16.9 ± 4.9 days postinjury). One night of ambulatory polysomnography was performed at bedside. Results . Compared to OSCI patients, TBI patients showed a significantly longer duration of nocturnal sleep and earlier nighttime sleep onset. Sleep efficiency was low and comparable in both groups. All sleep stages were observed in both groups with normal proportions according to age. Conclusion . Patients in the acute stage of severe TBI exhibit increased sleep duration and earlier sleep onset, suggesting that the injured brain enhances sleep need and/or decreases the ability to maintain wakefulness. As poor sleep efficiency could compromise brain recovery, further studies should investigate whether strategies known to optimize sleep in healthy individuals are efficacious in acute TBI. While there are several inherent challenges, polysomnography is a useful means of examining sleep in the early stage of recovery in patients with severe TBI.